Entrepreneurial marketing beyond professional marketing - Kotler, Philip; Kartajaya, Hermawan 1947-; Hooi, Den Huan (Wiley, 2023)
"Marketing legend Phil Kotler and his colleagues explain why the conventional "professional" approach to marketing is no longer enough. Marketers must be more entrepreneurial, creative, and risk-taking, if they are to adapt to the challenges of the post-pandemic digital world. Entrepreneurial Marketing explains the basics of professional marketing and marketing operations, but also how this foundation must support entrepreneurial thinking and risk-taking. This marriage of professional and entrepreneurship is the new capability marketers need to grow their companies in the next ten years. Each chapter starts with a global or regional case study"--
Includes index. - Description based upon online resource; title from PDF title page (viewed March 13th, 2023)
Keywords: Marketing -- Management; Organizational change; Decision making; Strategic planning; Creative ability in business; Marketing; Gestion; Changement organisationnel; Prise de décision; Planification stratégique; Créativité dans les affaires; decision making; Marketing; Management